Atmospheric mercury pollution caused by fluorescent lamp manufacturing and the associated human health risk in a large industrial and commercial city. (15th January 2021) - Luo, Qing; Ren, Yuxuan; Sun, Zehang; Li, Yu; Li, Bing; Yang, Sen; Zhang, Wanpeng; Hu, Yuanan; Cheng, Hefa
Abstract: Although already eliminated in most industrial processes, mercury, as an essential ingredient in all energy-efficient lighting technologies, is still used in fluorescent lamp manufacturing. This study was conducted to investigate the atmospheric pollution caused by fluorescent lamp production and assess the associated public health risk in a large industrial and commercial city of south China, Zhongshan, which is a major production hub of lighting products. Concentrations of total gaseous mercury (TGM) in the atmosphere were measured over a total of 342 sites in the industrial, commercial, and residential areas. The average levels of TGM in the industrial, commercial, and residential areas prior to the landing of a typhoon were 12 ± 11, 3.6 ± 2.1, and 2.7 ± 1.3 ng⋅m −3, respectively. TGM concentrations in the industrial areas exhibited significant diurnal variation, with levels in the working hours being much higher than those in the non-working hours, which indicates that the high atmospheric mercury concentrations were contributed by local emissions, instead of regional transport. Most fluorescent lamp manufacturing activities in the city were shut down during a typhoon event, which resulted in a significant reduction in the average TGM level (down to 1.6 ± 1.8 ng⋅m −3 ) and rendered the difference in the average TGM levels in the industrial areas no longer significant between the working and non-working hours. Elevated TGM levels (up to 49 ng⋅m −3 ) were found near clusters of small-scale fluorescent lamp workshops in both industrial and commercial areas, which is indicative of significant emissions of mercury vapor resulting from obsolete equipment and production technologies. No significant non-carcinogenic risk was found for the general residents in the sampling area over the study period, while the risk for the workers in the fluorescent lamp manufacturing facilities and workshops could be higher. These findings indicate that fluorescent lamp manufacturing in the developing countries is a major source of atmospheric mercury. Graphical abstract: Image 1 Highlights: Atmospheric Hg pollution caused by fluorescent lamp production was investigated. Industrial areas had much higher Hg levels than commercial and residential areas. Atmospheric Hg levels had diurnal variation and were strongly impacted by a typhoon. High atmospheric Hg levels resulted from emissions of local fluorescent lamp plants. The health risk from non-occupational exposure to the atmospheric Hg was acceptable. Abstract : Emissions from fluorescent lamp manufacturing activities resulted in elevated levels of atmospheric mercury, while inhalation exposure to the mercury posed no health risk for the general population.